Desenvolvimento e validação de método quimiométrico para determinação de amoxicilina em formulação farmacêutica - Silva, Maurício Alves de Melo (2011)
This work proposed a new method for determination of amoxicillin in suspension pharmaceutical formulations, based on transflectance NIR measurements and partial least squares multivariate calibration. A complete methodology was implemented for developing the proposed method, including experimental design with two independent factors (amoxicillin and placebo), data preprocessing by using multiple scatter correction, sample selection by Kennard-Stone algorithm, outlier detection based on high values of leverage, and X and Y residuals. The best model was obtained with seven latent variables in the range from 40.0 to 65.0 mg ml-1 of amoxicillin, providing a root mean square error of prediction of 1.6 mg ml-1. The method was validated in accordance with Brazilian and international guidelines, through the estimative of figures of merit, such as linearity, precision, accuracy, robustness, selectivity, analytical sensitivity, limits of detection and quantitation, and bias. A pseudo-univariate calibration curve was also obtained based on the net analyte signal. The proposed chemometric method presented the advantages of rapidity, simplicity, low cost, no use of solvents and no chemical waste generation over the main alternative methods based on high performance liquid chromatography.